9(3х-2)-6=5(4х-1)+2
27x - 18 - 6 = 20x - 5 + 2
27x - 20x = - 5 +2 + 18 + 6
7x = 21
x= 21 : 7
x= 3
Пошаговое объяснение:
1) y = g(x):
Область определения: [-2; 6]
Область значения: [-3; 2]
Нули при x ∈ {2, 6}
На [-2; 0) ∪ (4; 6] монотонно убывает.
На (0; 4) монотонно возрастает.
На [-2; 2) отрицательна.
На (2; 6) положительна.
В (0; -3) absmin.
В (4; 2) absmax.
2) y = f(x):
Область определения: [-5; 4]
Область значения: [-2; 4]
Нули при x ∈ {-3.5, 1, 3}
На (-1; 2) монотонно убывает.
На [-5; -1) ∪ (2; 4] монотонно возрастает.
На [-5; -3.5) ∪ (1; 3) отрицательна.
На (-3.5; 1) ∪ (3; 4] положительна.
В (2; -1.5) locmin.
В (-1; 4) absmax.
x=3
Пошаговое объяснение:
Раскроем скобки
27x-18-6=20x-5+2
27x-20x=-5+2+18+6
7x=21
x=3